Business Management Strategies in accordance with the Principles of Papanika in the Era of the Coronavirus Disease - 2019 (COVID - 2019) Pandemic - Karnasuta, Kanitda (MCU Haripunchai Review, 2021)
The coronavirus pandemic has disrupted many private businesses with government measures such as lockdown, social distancing, do not sit and eat in the restaurant, and close attractions and landmarks. If any government and non-governmental organizations have personnel infected with COVID-2019 must be quarantined for at least 14 days, etc. This situation directly affects business management. Although many private companies are able to go online, others are unable to adapt due to unfavorable business. However, business must continue in order to survive, so it must rely on principles of Papanika that can lead to formulating business management strategies perfectly, namely: 1) Chakkuma is an organization that has a vision to innovate smart business channels, especially product knowledge that can reduce costs from products and have a channel to quickly discharge inventories, 2) Vidhuro is the expertise and clarity in the marketing mechanism in the COVID -2019 era, the market system, the needs of consumers, the ability to clearly define the target group, the ability to continually win the hearts of customers for that product that meets the needs of customers, and 3) Nissaya Sampanno is the image of a business organization that is credible, sincere, honest to customers, trustworthy, and it has a continuous source of funds or money flow in the organization.